A Review of the Influence of Group Goals on Group Performance - O’Leary-Kelly, Anne M.; Martocchio, Joseph J.; Frink, Dwight D. (Academy of Management Journal, 1994)
This research combined meta-analytic and narrative review methods in an effort to assess the influence of group goals on group performance. The meta-analytic review revealed a strong group goal effect. The narrative review discusses the generalizabilily of the group goal effect and provides suggestions for designing future group goal-setting research.